Antioxidant Release Profile from Chitosan/ĸ-Carrageenan-based Polyelectrolyte Complex Films as Active Packaging: A Preliminary Study - Rahmasari, Khusna Santika; Ishartono, Bayu (Universitas Jenderal Soedirman, 2024)
Significant efforts are necessary to prevent the spoilage of fatty acid-rich foods as a result of lipid oxidation. Active packaging is a technology that employs packaging films containing antioxidants to increase the stability of perishable foods susceptible to oxidation. This preliminary study aimed to incorporate tannic acid (TA) into a chitosan/κ-carrageenan (Chit/κ-Car)-based polyelectrolyte complex (PEC) films and evaluate their antioxidant release profile. The composition of Chit/κ-Car, glycerol (gly), and TA in PEC films were also investigated in this preliminary study as factors influencing the mechanical properties of films and the antioxidant release profile. The prepared PEC films were identified by an FTIR spectrometer and examined through a mechanical property test. The DPPH method was used to assess the antioxidant property of the Chit/κ-Car-based PEC films. The infrared spectra revealed that PEC films were formed through the interaction between ꟷNH3+ of Chit and ꟷOSO3ꟷ of κ-Car. Increasing the κ-Car and TA compositions in the PEC films increased the tensile strength (TS) and water absorption capacity (WAC), but decreased the elongation (E). The release profile of TA from PEC films followed the Korsmeyer-Peppas model through the Fickian diffusion mechanism with n < 0.5. The antioxidant activity test of PEC films using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method revealed high antioxidant activity with radical scavenging activity (RSA) values up to 95.04%. As a result, the Chit/κ-Car-based PEC films have the potential to be developed as active packaging. Keywords: Active packaging, antioxidant, Chit/κ-Car-based PEC films, release profile, TA